A surprise visitor / Carolyn Soo - Soo, Carolyn (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
How are you today dear visitor? Lorong APB level 3, had not expected your benevolent visit Indeed a surprise, A wonder... That you should decide to grace us In our mundane work, Correcting papers, Attending meetings, Clocking in and clocking out, Lecturers like us do this Dedicated and hardworking, KPIs and deadlines, Tomorrow is another day We scream, We laugh, and We wonder, Little visitor... Biawak oh! Why are you still here Day after day, I see, You are not distracted by us.